Effects of Peripheral Visual Field Loss on Eye Movements During Visual Search - Wiecek, Emily; Pasquale, Louis R.; Fiser, Jozsef; Dakin, Steven; Bex, Peter J. (Frontiers in Psychology, 2012)
Natural vision involves sequential eye movements that bring the fovea to locations selected by peripheral vision. How peripheral visual field loss (PVFL) affects this process is not well understood. We examine how the location and extent of PVFL affects eye movement behavior in a naturalistic visual search task. Ten patients with PVFL and thirteen normally sighted subjects with full visual fields (FVF) completed 30 visual searches monocularly. Subjects located a 4 x 4 degree target, pseudo-randomly selected within a 26 x 11 degree natural image. Eye positions were recorded at 50 Hz. Search duration, fixation duration, saccade size, and number of saccades per trial were not significantly different between PVFL and FVF groups (p > 0.1). A Chi-square test showed that the distributions of saccade directions for PVFL and FVL subjects were significantly different in 8 out of 10 cases (p < .01). Humphrey Visual Field pattern deviations for each subject were compared with the spatial distribution of eye movement directions. There were no significant correlations between saccade directional bias and visual field sensitivity across the 10 patients. Visual search performance was not significantly affected by peripheral visual field loss. An analysis of eye movement directions revealed patients with PVFL show a biased directional distribution that was not directly related to the locus of vision loss, challenging feed-forward models of eye movement control. Consequently, many patients do not optimally compensate for visual field loss during visual search.